Changes in Female Employment in Mexico : Demographics, Economics, and Policies - Lopez-Acevedo, Gladys; Freije-Rodriguez, Samuel; Vergara Bahena, Mexico Alberto; Cardozo Medeiros, Diego (World Bank, Washington, DC, 2020)
The unemployment and labor force participation gender gaps narrowed in Mexico after the 2008 global economic crisis, when female labor force participation increased. This paper aims to understand female labor force participation growth and identify its main determinants. For that purpose, the paper estimates a probit model with data from the National Employment Survey of 2007 and 2017, when the unemployment rate returned to the pre-crisis level. Broadly, the results show that increasing labor force participation of women ages 36 to 65 sustained the growth of overall female labor force participation, women's educational attainment can offset any individual or household obstacle to women's employability, and childcare availability significantly supports mothers' employability.